Comparative analysis of entrepreneurial traits of maize growers in Purnea region of Bihar - SHARMA, N K; NAG, ARINDAM; KUMAR, PANKAJ; MAHTO, D K; SINGH, ANIL KUMAR (The Indian Journal of Agricultural Sciences, 2026)
Maize (Zea mays L.) is an important cereal crop, ranking 3rd after rice and wheat for socio-economic development of the Indian farmers. The cultivation of winter (rabi) maize has increased significantly over the last decade in Bihar; consequently entrepreneurial opportunities in this sector are also expanding. Against this backdrop, the present study was carried out during 2022 and 2023 to compare entrepreneurial traits of the maize growers across all the four districts of Purnea region: Purnea, Araria, Katihar and Kishanganj. Data were collected by conducting face to face interview with randomly selected 120 farmers with the help of pre constructed semi-structured interview schedule. The results revealed that 34.16% of maize growers in Purnea region possessed medium high level of entrepreneurial traits, while 30.00% and 5.38% of the maize growers displayed high and very high level of entrepreneurial traits, respectively. ANOVA results indicated significant differences among the districts. Katihar ranked first in terms of adoption leadership and independency whereas Araria was ranked first based on risk bearing capacity, achievement motivation, self-control and competitiveness. Maize growers in the Purnea district showed significantly higher score based on innovativeness. The study suggests that education combined with larger landholdings under maize cultivation and an improved irrigation index, will enhance the entrepreneurial behaviour of the maize growers in Purnea region.